A method for preparing organic fertilizer from silkworm excrement in an industrialized breeding silkworm excrement subcritical water harmless resource

CN122940490APending Publication Date: 2026-10-20SANWEI ECOLOGICAL TECHNOLOGY (HAIKOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611210644.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

对于一般畜禽粪污,上述方式可在一定程度上降低腐败风险并转化部分有机质;但对于工业化养殖蚕沙,常规堆肥周期较长,处理过程受环境温度、含水率、通气条件和原料波动影响较大,对颗粒内部抗生素残留和有害微生物等风险因子的削减不够稳定

Benefits of technology

[0022](1)本发明采用连续处理方式,使蚕沙颗粒形成有利于水热介质进入的表层微通道,再进行内部均匀无害化处理,并在所得多孔固相中实现营养组分的内渗负载和稳定保持;与单纯水热处理或水热后直接喷洒营养液的常规方式相比,本发明通过改善颗粒内部传质状态和营养固定状态,解决蚕沙颗粒营养主要停留于表层以及成品养分易淋失的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

This invention discloses a method for preparing organic fertilizer from industrially raised silkworm excrement using subcritical water in a harmless and resource-efficient manner, belonging to the field of organic fertilizer preparation technology. The method includes: removing impurities, breaking down, sieving, and adjusting the moisture content of industrially raised silkworm excrement; mixing it with an anti-caking and permeable pre-conditioning solution containing organic acids, potassium humate or potassium fulvate, a non-sodium wetting and dispersing agent, and water; further treating it with a hydrothermal reaction medium containing organic acids and potassium humate or potassium fulvate under subcritical hydrothermal conditions, resulting in solid-liquid separation to obtain a permeable silkworm excrement solid phase with interconnected pores and liquid absorption capacity; subjecting it to vacuum-positive pressure pulse impregnation with an organic nutrient mother liquor, followed by wet heat setting, drying, and molding to obtain silkworm excrement-based organic fertilizer. This invention synergistically opens the internal mass transfer channels of silkworm excrement particles through weak acid pre-conditioning, humic substance dispersion, and subcritical hydrothermal dissolution, reducing the risk of antibiotic residues, harmful microorganisms, and the spread of resistance genes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic fertilizer preparation technology, and in particular to a method for preparing organic fertilizer from subcritical water of industrially raised silkworm excrement in a harmless and resource-efficient manner. Background Technology

[0002] Industrialized silkworm excrement is a continuous organic solid byproduct generated during large-scale silkworm rearing. It mainly consists of silkworm excrement, residual mulberry leaves, feed residue, silkworm secretions, and a small amount of bedding material. It is characterized by high levels of organic matter, nitrogen, phosphorus, potassium, and residual organic components from mulberry leaves, possessing the potential for resource-based organic fertilizer production. However, industrialized silkworm excrement differs from ordinary silkworm excrement or general agricultural organic waste. Originating from a high-density, continuous rearing environment, it may contain risk factors such as antibiotic residues, harmful microorganisms, insect eggs, and insufficiently stabilized organic components. If it is directly used as fertilizer without adequate treatment, it may pose risks to microbial safety, plant safety, and the soil environment.

[0003] In existing technologies, the harmless and resource-based treatment of livestock waste typically employs methods such as composting, aerobic maturation, high-temperature sterilization, steam curing, conventional hydrothermal treatment, or granulation with the addition of conditioning agents. For general livestock manure, these methods can reduce the risk of spoilage and convert some organic matter to a certain extent. However, for industrially raised silkworm excrement, conventional composting cycles are long, and the treatment process is significantly affected by environmental temperature, moisture content, ventilation conditions, and raw material fluctuations, resulting in insufficient and unstable reduction of risk factors such as antibiotic residues and harmful microorganisms within the granules. Simply increasing the hydrothermal temperature or extending the treatment time can enhance the surface treatment intensity, but it is difficult to solve the problem of insufficient internal mass transfer caused by rapid sealing of the granule surface, and may lead to excessive carbonization of organic matter, nitrogen loss, material adhesion and agglomeration, and a decline in subsequent granulation performance. Especially under high-temperature, closed-loop treatment conditions, the introduction of foaming components that easily release additional gases increases the complexity of pressure sources and the difficulty of industrial safety control, which is detrimental to continuous and stable production.

[0004] Therefore, there is an urgent need to develop a method to improve the permeability of the particle surface before hydrothermal treatment, achieve uniform and harmless treatment inside and outside the particles during hydrothermal treatment, and achieve the internal loading and stable shaping of nutrient components in the subsequent fertilizer preparation process. Summary of the Invention

[0005] This invention overcomes the shortcomings of the prior art and provides a method for the harmless and resource-based preparation of organic fertilizer from subcritical water used in industrialized silkworm farming.

[0006] To achieve the above objectives, the technical solution adopted by this invention is: a method for the harmless and resource-based preparation of organic fertilizer from subcritical water used in industrialized silkworm excrement farming, comprising:

[0007] S1: The silkworm excrement from industrialized breeding is subjected to impurity removal, breaking down, screening and moisture content adjustment to obtain pretreated silkworm excrement;

[0008] S2: Pretreated silkworm excrement is mixed with an anti-crusting and permeability preconditioning solution containing organic acids, potassium humate or potassium fulvate, non-sodium wetting and dispersing agent and water to obtain preconditioned silkworm excrement;

[0009] S3: Pre-conditioned silkworm excrement and a hydrothermal reaction medium containing organic acids and potassium humate or potassium fulvate are placed in a closed hydrothermal reactor. Subcritical hydrothermal treatment is carried out at 135℃~175℃, with a pressure of 0.60MPa~1.80MPa gauge pressure inside the reactor, and the hydrothermal reaction medium is kept in a continuous liquid phase at the corresponding treatment temperature. After solid-liquid separation, a permeable silkworm excrement solid phase is obtained.

[0010] S4: Vacuum-positive pressure pulse impregnation of permeable silkworm excrement solid phase with organic nutrient mother liquor to obtain nutrient-loaded material;

[0011] S5: The nutrient-loaded material is subjected to wet heat setting, drying and molding treatment to obtain silkworm excrement-based organic fertilizer.

[0012] In a preferred embodiment of the present invention, in step S1, the pretreated silkworm excrement has a particle size of 0.5 mm to 6.0 mm and a moisture content of 25% to 45%.

[0013] In a preferred embodiment of the present invention, in step S2, the organic acid is one or more of citric acid, malic acid, and lactic acid; the potassium humate or potassium fulvate is a water-soluble potassium source of humic acid or fulvate; and the non-sodium wetting and dispersing agent is one or more of calcium lignosulfonate, magnesium lignosulfonate, ammonium lignosulfonate, potassium polyglutamate, calcium polyglutamate, magnesium polyglutamate, and molasses fermentation broth concentrate.

[0014] In a preferred embodiment of the present invention, based on the dry weight of pretreated silkworm excrement, the amount of organic acid added is 0.2% to 1.5%, the amount of potassium humate or potassium fulvate added is 0.2% to 1.2%, and the amount of non-sodium wetting and dispersing agent added is 0.05% to 0.5%; the pH of the anti-caking and permeability preconditioning solution is 4.8 to 6.5, and the amount used is 8% to 35% of the dry weight of pretreated silkworm excrement, and the moisture content of the preconditioned silkworm excrement is 35% to 55%.

[0015] In a preferred embodiment of the present invention, in step S3, the hydrothermal reaction medium includes 0.03% to 0.30% organic acid and 0.05% to 0.50% potassium fulvate or potassium humate, with the remainder being water; the mass ratio of pre-conditioned silkworm excrement to the hydrothermal reaction medium is 1:(0.25 to 0.80), and the subcritical hydrothermal treatment time is 20 min to 35 min.

[0016] In a preferred embodiment of the present invention, in step S4, the organic nutrient mother liquor is prepared from one or more of the following: hydrothermal effluent from livestock and poultry manure, concentrated biogas slurry, amino acid fermentation broth, humic acid broth, and seaweed extract; the organic nutrient mother liquor has a pH of 5.5 to 7.5, a solid content of 3% to 15%, a total nitrogen content of 0.3% to 3.0%, and a humic acid or fulvic acid content of 0.2% to 5.0%.

[0017] In a preferred embodiment of the present invention, in step S4, the mass ratio of the permeable silkworm excrement solid phase to the organic nutrient mother liquor is 1:(0.3-1.2), and the impregnation temperature is 50℃-85℃.

[0018] In a preferred embodiment of the present invention, the vacuum-positive pressure pulse impregnation treatment in step S4 includes: evacuating to a gauge pressure of -0.08MPa to -0.04MPa and holding for 3 min to 10 min; increasing the pressure to a gauge pressure of 0.05MPa to 0.40MPa and holding for 3 min to 10 min; the evacuation and pressure increase process is repeated 1 to 4 times.

[0019] In a preferred embodiment of the present invention, in step S5, the wet heat setting temperature is 105℃~145℃, the pressure is gauge pressure 0.15MPa~0.60MPa, and the processing time is 10min~35min; the drying temperature is 55℃~85℃, and the product moisture content is dried to 12%~25%. After drying, the material is subjected to disc granulation, extrusion granulation, drum granulation, or sieving to obtain granular or powdered silkworm excrement-based organic fertilizer.

[0020] In a preferred embodiment of the present invention, after the vacuum-positive pressure pulse impregnation in step S4 and before the wet heat setting in step S5, minerals and adsorbent fertilizer-retaining conditioning components are added to the nutrient-loaded material. The minerals and adsorbent fertilizer-retaining conditioning components are one or more of calcium silicate, magnesium silicate, calcium magnesium silicate, dolomite powder, diatomaceous earth, sepiolite powder, zeolite powder, bentonite, and biochar powder. The amount added is 1.0% to 10.0% of the dry basis mass of the nutrient-loaded material.

[0021] This invention addresses the shortcomings of the prior art and has the following beneficial effects:

[0022] (1) The present invention adopts a continuous processing method to form surface microchannels that facilitate the entry of hydrothermal medium into the silkworm excrement particles, and then performs internal uniform and harmless treatment, and realizes the internal infiltration loading and stable maintenance of nutrient components in the obtained porous solid phase. Compared with the conventional method of simple hydrothermal treatment or direct spraying of nutrient solution after hydrothermal treatment, the present invention solves the problem that the nutrients of silkworm excrement particles mainly stay on the surface and the nutrients of the finished product are easily lost by improving the internal mass transfer state and nutrient fixation state of the particles.

[0023] (2) Before hydrothermal treatment, the present invention pre-conditions the silkworm excrement with an anti-crusting and permeability-enhancing pre-conditioning liquid containing organic acids, potassium humate or potassium fulvate, and wetting and dispersing agents. The organic acids keep the surface of the silkworm excrement particles in a weakly acidic to near-neutral environment, reducing the rapid browning and adhesion of surface proteins, sugars, and fiber components in the early stage of heating. The organic acids regulate the weakly acidic environment of the particle surface and soften the organic cement structure. Potassium humate or potassium fulvate and non-sodium wetting and dispersing agents improve the liquid phase spreading, disperse the colloidal hydrolysis products generated during hydrothermal treatment, and reduce the tendency of surface browning, adhesion, and crusting. Subcritical hydrothermal treatment promotes the migration of some soluble organic components to the liquid phase, opening and connecting the original fiber gaps, capillary channels, and micropores of the silkworm excrement. Compared with ordinary hydrothermal treatment without anti-crusting and permeability-enhancing pre-conditioning, the present invention avoids the problem of the hydrothermal medium being blocked by a dense surface layer, and makes the subsequent hydrothermal treatment proceed uniformly from the particle surface to the interior.

[0024] (3) In this invention, pre-conditioned silkworm excrement is subjected to subcritical hydrothermal treatment with a hydrothermal reaction medium containing organic acids and potassium humate or potassium fulvate at 135℃~175℃ and a gauge pressure of 0.6MPa~1.8MPa. The hydrothermal reaction medium enters the interior of the granules along the channel. The organic acids promote the moderate hydrolysis of proteins, hemicellulose, mulberry leaf residues and chitin-related components inside the silkworm excrement. The fulvate or humate disperses the small molecule organic matter and colloidal substances generated by hydrolysis, reducing the re-blocking of internal pores, improving the hydrothermal contact state inside the granules, and improving the uniformity and thoroughness of the internal harmless treatment. Compared with the existing technology, which simply increases the hydrothermal temperature or extends the treatment time, it is still easy to cause excessive surface treatment and insufficient internal treatment. This invention reduces the risk of antibiotic residues, relative abundance of resistance genes and harmful microbial residues inside the granules within a shorter hydrothermal treatment time, and reduces the fluctuation of fertilizer safety caused by insufficient local treatment.

[0025] (4) The present invention obtains a permeable silkworm excrement solid phase after subcritical hydrothermal treatment, and then impregnates the permeable silkworm excrement solid phase with an organic nutrient mother liquor under vacuum-positive pressure pulse. During the vacuum stage, the air and some water vapor in the pores of the permeable silkworm excrement solid phase are discharged. During the positive pressure stage, the organic nutrient mother liquor is pushed into the pores of the particles. Multiple pulses further improve the degree of penetration of the nutrient mother liquor into the deep pores, and improve the liquid absorption load and load uniformity of the organic nutrient mother liquor inside the silkworm excrement particles. Compared with the method of soaking under normal pressure or directly spraying nutrient solution after hydrothermal treatment, the present invention reduces the situation where the nutrient components only adhere to the outer surface of the particles, and allows more organic nitrogen, humic substances, soluble potassium and other organic active components to enter the interior of the particles, providing a structural basis for subsequent stable maintenance and slow release.

[0026] (5) The present invention performs wet heat setting treatment on the nutrient-loaded material, so that the nutrient components such as humic acid, fulvic acid, amino acids, small molecule organic acids, ammonium nitrogen and soluble potassium salts that enter the permeable silkworm excrement solid phase are adsorbed, complexed, hydrogen bonded and partially condensed and fixed with cellulose, hemicellulose, chitin hydrolysate fragments and mineral ash in the silkworm excrement particles under wet heat conditions. This changes the nutrient components from a simple liquid filling state to a state held by a pore network and organic colloids, improves the nutrient retention rate during the drying process and reduces the short-term nutrient loss of the finished product under water immersion conditions. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 This is a flowchart of a preferred embodiment of the present invention. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention is also practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0031] Source of materials:

[0032] Industrialized silkworm excrement comes from large-scale silkworm rearing workshops, where plastic sheets, metal wires, stones, large sections of mulberry branches, and packaging fragments are removed before the raw materials enter the processing line.

[0033] Citric acid, malic acid, and lactic acid can be sourced from industrial-grade or food fermentation by-product raw materials, purchased from Jinan Leihe Trading Co., Ltd.

[0034] Potassium humate and potassium fulvate are water-soluble fertilizer raw materials purchased from Wuhan Jiyesheng Chemical Co., Ltd.

[0035] Lignosulfonate, polyglutamate, and molasses fermentation broth concentrate can be obtained from commonly used wettable and dispersible raw materials in fertilizer production. The lignin sulfonate was purchased from Hubei Xinmingtai Chemical Co., Ltd., the polyglutamate was purchased from Hubei Guangao Biotechnology Co., Ltd., and the molasses fermentation broth was purchased from Nanning Hua Trade Co., Ltd.

[0036] The organic nutrient mother liquor is prepared from one or more of the following: hydrothermal effluent from livestock and poultry manure, concentrated biogas slurry, amino acid fermentation broth, humic acid solution, and seaweed extract. When hydrothermal effluent from livestock and poultry manure is used as the organic nutrient mother liquor, the raw material of livestock and poultry manure or livestock and poultry manure slurry is mixed with water at a mass ratio of 1:1.5, and the water content of the system is adjusted to enable pumping and stirring. The mixed slurry is treated at 120℃~150℃ and a gauge pressure of 0.20MPa~0.50MPa for 20min~40min. After treatment, the liquid phase is obtained by solid-liquid separation, filtered through 80-120 mesh, and humic acid solution or fulvic acid solution is added to adjust the content of soluble humic acid substances to obtain the organic nutrient mother liquor. The pH of the organic nutrient mother liquor from livestock and poultry manure is controlled at 5.5~7.5, the solid content is controlled at 3%~15%, the total nitrogen content is controlled at 0.3%~3.0%, and the humic acid or fulvic acid content is controlled at 0.2%~5.0%.

[0037] When using biogas slurry concentrate as the organic nutrient mother liquor, large suspended solids and unstable organic residues should be removed first. Biogas slurry concentrate has a high ammonium nitrogen content, making it suitable for use in conjunction with humic acid solution. When using amino acid fermentation liquid, its soluble organic nitrogen content is high, but its salt content is also high. It is suitable for partially replacing chicken manure hydrothermal liquid, but not for use as the sole nutrient mother liquor.

[0038] When seaweed extract is used in organic nutrient mother liquor, its main function is to provide soluble polysaccharides, alginate and trace active components to improve the water retention and root-friendly properties of the finished product in substrate applications. When the viscosity of seaweed extract is high, it should be diluted with hydrothermal fluid or humic acid solution before vacuum-positive pressure pulse impregnation to avoid a decrease in internal penetration efficiency.

[0039] In continuous production, organic nutrient mother liquor is prepared centrally and stored at a temperature controlled between 35℃ and 55℃. Too low a temperature will cause humic acid substances and fine mineral powder to settle, while too high a temperature will accelerate the conversion of ammonium nitrogen into free ammonia and promote the regeneration of microorganisms. The storage tank should be equipped with low-speed circulation or intermittent stirring to keep the nutrient mother liquor uniform before it enters the impregnation unit.

[0040] The mineral and adsorbent fertilizer-preserving conditioning components are selected from one or more of zeolite powder, bentonite, biochar powder, and sepiolite powder. After vacuum-positive pressure pulse impregnation and before wet heat setting, the nutrient load material is added. The amount added is 1.0% to 10.0% of the dry basis mass of the nutrient load material, preferably 3.0% to 8.0%. After addition, the mixture is mixed and dispersed for 10 min to 30 min.

[0041] The specific processing steps are as follows: In step S1, the collected industrially raised silkworm excrement is broken up after being screened by a drum screen, vibrating screen or air classifier to restore the agglomerated silkworm excrement to a mixable granular state. The particle size of the screened silkworm excrement is controlled to be 0.5mm to 6.0mm. If the particle size is too large, the subsequent anti-caking and permeability pre-conditioning liquid will have difficulty entering the particle surface in a short time, and the internal uniformity after hydrothermal treatment will decrease. If the particle size is too small, the material is prone to forming mud-like agglomerates during the humidification and hydrothermal treatment process, which will affect solid-liquid separation and granulation.

[0042] The moisture content of pretreated silkworm excrement should be controlled between 25% and 45%. When the moisture content is below 25%, the surface of the particles is relatively dry, and the anti-caking and permeable pre-conditioning liquid does not make sufficient contact with the surface of the particles, making it easy for dry powder to form locally. When the moisture content is above 45%, there is too much free water in the material, which makes it easy for clumping and slurrying to occur during mixing, which is not conducive to the subsequent formation of uniform pre-conditioned silkworm excrement.

[0043] Pretreated silkworm excrement should be in a uniform and loose state, with no obvious mud clumps between particles. It should clump together when squeezed but crumble easily when touched. This is conducive to the uniform coating of the particle surface by the anti-caking and permeable pre-conditioning liquid during short-term mixing, as well as the subsequent entry of the hydrothermal reaction medium along the gaps between particles and the pores on the particle surface.

[0044] In step S2, an anti-crusting and permeability preconditioning solution is prepared by mixing organic acid, potassium humate or potassium fulvate, non-sodium wetting and dispersing agent and water. During preparation, the organic acid is first dissolved in water, then potassium humate or potassium fulvate is added and stirred until there are no obvious lumps. Then, the non-sodium wetting and dispersing agent is added, mixed evenly, and sprayed onto the pretreated silkworm excrement.

[0045] If the moisture content of the pretreated silkworm excrement is close to 25%, the amount of anti-caking and permeability-enhancing pre-conditioning solution can be appropriately increased to fully wet the surface of the particles. If the moisture content of the pretreated silkworm excrement is close to 45%, the amount of anti-caking and permeability-enhancing pre-conditioning solution should be reduced and the concentration of effective components in the anti-caking and permeability-enhancing pre-conditioning solution should be increased to avoid material slurrying. After the pre-conditioning and mixing is completed, it is preferable to enter the subcritical hydrothermal treatment within 30 minutes to reduce the decrease in surface permeability caused by uneven migration of the pre-conditioning solution, particle re-agglomeration, or local water loss.

[0046] This step does not use additional gas-generating foaming as a permeation source, avoiding the introduction of non-steam pressure sources in a closed high-temperature environment, which would increase the complexity of pressure control. The role of the anti-crust permeation preconditioning liquid is to regulate the weakly acidic environment on the surface, soften the organic cement structure, improve the liquid phase spreading and disperse hydrolyzed colloids, and create conditions for subsequent subcritical hydrothermal entry into the particle interior.

[0047] Based on the dry weight of pretreated silkworm excrement, the amount of organic acid added is 0.2%–1.5%. Organic acid keeps the surface of the silkworm excrement particles in a weakly acidic to near-neutral state, inhibiting rapid browning and adhesion of surface organic components during the initial stage of humid heating. If the addition amount is less than 0.2%, the surface pH control is insufficient; if the addition amount is greater than 1.5%, some alkaline nutrients in the subsequent organic nutrient mother liquor will be excessively neutralized, resulting in a low pH in the finished product. The addition amount of potassium humate or potassium fulvate is 0.2%–1.2%, preventing the formation of a continuous adhesive film by the organic colloids on the surface of the silkworm excrement during mixing and heating. The addition amount of wetting and dispersing agent is 0.05%–0.5%, used to reduce the spreading resistance of the anti-caking and permeability pre-conditioning liquid on the surface of the silkworm excrement particles and increase the rate at which the liquid phase enters the shallow pores of the particles.

[0048] The mixing temperature in step S2 is 45℃~70℃, and the mixing time is 5min~15min. This temperature range reduces the viscosity of the liquid, softens the organic matter on the surface of the particles, and promotes the entry of the pre-conditioning components into the shallow pores. The surface of the pre-conditioned silkworm excrement obtained after mixing is moist.

[0049] Step S3 involves placing pre-conditioned silkworm excrement and a hydrothermal reaction medium containing organic acids and potassium humate or potassium fulvate in a closed hydrothermal reactor. Subcritical hydrothermal treatment is carried out at 135℃~175℃, with a pressure of 0.60MPa~1.80MPa gauge pressure inside the reactor, and the hydrothermal reaction medium is kept in a continuous liquid phase at the corresponding treatment temperature. After solid-liquid separation, a permeable silkworm excrement solid phase is obtained.

[0050] The mass ratio of pre-conditioned silkworm excrement to hydrothermal reaction medium is 1:(0.25~0.80). When the material-liquid ratio is less than 1:0.25, the hydrothermal reaction medium is insufficient, and the mass and heat transfer inside the particles is inadequate. When the material-liquid ratio is greater than 1:0.80, the amount of hydrothermal liquid phase generated is too large, the subsequent solid-liquid separation load increases, and the proportion of soluble nutrients lost with the liquid phase increases.

[0051] The subcritical hydrothermal treatment temperature is controlled at 135℃~175℃, preferably 145℃~165℃; the pressure is controlled at gauge pressure of 0.6MPa~1.80MPa; and the treatment time is controlled at 20min~35min, preferably 30min. Saturated steam heating is preferred during the treatment process to ensure uniform heating of the system and reduce local overheating, carbonization, and ammonia volatilization.

[0052] Under subcritical hydrothermal conditions, some proteins, hemicellulose, mulberry leaf residues, and chitin-related components inside the silkworm excrement particles undergo moderate hydrolysis, while some soluble organic components and colloidal components enter the liquid phase. At the same time, the weakly acidic environment and the dispersion effect of humus reduce the tendency of surface crusting and pore re-clogging, and the original fiber gaps, capillary channels, and micropores inside the particles are further opened. After solid-liquid separation, a permeable silkworm excrement solid phase with interconnected pores and liquid absorption capacity is obtained.

[0053] During the subcritical hydrothermal treatment, the weakly acidic, wettable, and dispersible environment formed in step S2 reduces the tendency of the particle surface to crust and the hydrolytic colloids to block it. This allows the hydrothermal reaction medium to be transferred to the interior along the original fiber gaps, capillary channels, and micropores of the silkworm excrement particles. The weakly acidic organic acids promote the moderate hydrolysis of some proteins, hemicellulose, mulberry leaf residues, and chitin-related components. Potassium humate has a dispersing effect on the small molecule organic matter and colloidal substances produced by hydrolysis, reducing the blockage of pores by sticky byproducts. After the treatment, the silkworm excrement particles change from an outer layer with a tendency to be closed to a porous solid with the ability to absorb liquid inside.

[0054] After subcritical hydrothermal treatment, the material is subjected to spiral filter press, belt filter press, centrifugal separation or other solid-liquid separation methods to obtain permeable silkworm excrement solid phase and hydrothermal liquid phase. The moisture content of the permeable silkworm excrement solid phase is controlled at 45% to 65%. Too low a moisture content will reduce the infiltration efficiency of the subsequent nutrient mother liquor, while too high a moisture content will dilute the organic nutrient mother liquor and increase the shaping and drying load.

[0055] Step S4 involves vacuum-positive pressure pulse impregnation of the permeable silkworm excrement solid phase and the organic nutrient mother liquor. The organic nutrient mother liquor used in this step preferably has a pH of 5.5–7.5, a solid content of 3%–15%, a total nitrogen content of 0.3%–3.0%, a humic acid or fulvic acid content of 0.2%–5.0%, an electrical conductivity not exceeding 15 mS / cm, and a viscosity not exceeding 200 mPa·s at 25°C. It is then filtered through an 80-120 mesh filter or subjected to equivalent solid-liquid dispersion treatment. The mass ratio of the permeable silkworm excrement solid phase to the organic nutrient mother liquor is 1:(0.3–1.2), and the mixing temperature is controlled at 50°C–85°C. At lower temperatures, the viscosity of the nutrient mother liquor is higher, and the infiltration rate decreases; at higher temperatures, some ammonium nitrogen is converted to free ammonia and volatilizes, and the loss of low-molecular-weight organic active components increases.

[0056] Vacuum-positive pressure pulse impregnation includes a vacuuming stage and a pressurization stage. In the vacuuming stage, the system pressure is reduced to -0.08 MPa to -0.04 MPa (gauge pressure) and maintained for 3 to 10 minutes, allowing air and some water vapor to escape from the pores of the permeable silkworm excrement solid phase. In the pressurization stage, the system pressure is increased to 0.05 MPa to 0.40 MPa (gauge pressure) and maintained for 3 to 10 minutes, allowing the organic nutrient solution to enter the particle pores under pressure. The vacuuming and pressurization processes are repeated 1 to 4 times. Vacuum-positive pressure pulse impregnation reduces the obstruction of residual air inside the particles to liquid entry. The first pulse allows the nutrient solution to enter larger pores and surface cracks, while subsequent pulses further propel the liquid into deeper pores and improve load uniformity.

[0057] After vacuum-positive pressure pulse impregnation, the nutrient-loaded material should be in a moist granular state with no large amount of free liquid on the surface. If obvious free liquid appears, it indicates that the amount of organic nutrient mother liquor added is too high or the pore loading capacity is insufficient. The material-liquid ratio should be reduced, the degree of solid-liquid separation should be increased, or the pore-forming preconditioning parameters should be adjusted to solve the problem. If the material surface is dry but the internal loading is insufficient, it indicates that the negative pressure exhaust or positive pressure propulsion is insufficient. The pulse time should be extended or the number of repetitions should be increased.

[0058] Step S5 involves moist heat setting of the nutrient load material. Before moist heat setting, the moisture content of the nutrient load material should be controlled at 45% to 70%, and it should be in a moist granular state with no continuous free liquid on the surface. Moist heat setting can be carried out in a saturated steam environment or a closed self-generated moist heat environment. The setting temperature is 105℃ to 145℃, the pressure is gauge pressure of 0.15MPa to 0.60MPa, and the processing time is 10min to 35min, which is used to stabilize the structure of the nutrient load.

[0059] During the humid heat setting process, humic acid, fulvic acid, amino acids, small molecule organic acids, ammonium nitrogen, and soluble potassium salts that enter the permeable silkworm excrement solid phase undergo adsorption, complexation, hydrogen bonding, and partial condensation fixation with cellulose, hemicellulose, chitin hydrolysate fragments, and mineral ash in the silkworm excrement particles under the action of humid heat. This transforms the nutrient components from a simple liquid-filled state to a state jointly maintained by the porous network and organic colloids.

[0060] When the wet heat setting temperature is below 105℃, the internal structure of the material is not sufficiently stabilized, increasing the risk of pulverization and nutrient loss after drying. When the temperature is above 145℃, some ammonium nitrogen is converted into free ammonia and volatilized, and the loss of low-molecular-weight active substances increases, while the nutrient mother liquor undergoes excessive browning on the particle surface, forming a hard shell. The set material can be dehydrated by flash evaporation using residual heat, and then dried at 55℃~85℃. Too high a drying temperature will increase nitrogen loss and particle surface hardening, while too low a temperature will result in excessively long drying time and increase the risk of mold growth.

[0061] The dried material can be processed by disc granulation, extrusion granulation, drum granulation, or sieving according to product form requirements. When preparing granular fertilizer, a small amount of hydrothermal liquid phase, humic acid solution, or organic nutrient mother liquor can be used as the granulation wetting liquid; when preparing powdered fertilizer, it should be directly sieved to the target particle size; the final product should be cooled to near ambient temperature and then sealed and packaged to reduce the risk of moisture absorption and clumping; the organic nutrient mother liquor should be tested for hygiene and safety and salt content before use; Salmonella should not be detected, fecal coliforms should meet the requirements of the target fertilizer product, and antibiotic residues, sodium salts, and chloride salts should meet the predetermined product control requirements.

[0062] Example 1:

[0063] This embodiment uses industrialized silkworm excrement from a facility-based silkworm rearing workshop as raw material. The industrialized silkworm excrement is manually sorted, drum-screened, and air-separated to remove impurities such as plastic sheets, metal wires, stones, large pieces of mulberry branches, and packaging fragments. Subsequently, the clumps of silkworm excrement are mechanically broken up and screened to obtain silkworm excrement with a particle size of 1.0 mm to 4.0 mm. The moisture content is adjusted to 34.0% to obtain pretreated silkworm excrement in a uniform and loose state.

[0064] Based on the dry weight of pretreated silkworm excrement, an anti-caking and permeable pre-conditioning solution was prepared, wherein citric acid was added at 0.80%, potassium humate at 0.60%, calcium lignosulfonate at 0.18%, and the remainder was water; the pH of the anti-caking and permeable pre-conditioning solution was adjusted to 5.6 using citric acid, and the total amount of the anti-caking and permeable pre-conditioning solution was 20.0% of the dry weight of pretreated silkworm excrement.

[0065] During preparation, citric acid is added to water and stirred to dissolve, then potassium humate is added and stirred until no obvious lumps are formed. Calcium lignosulfonate is then added and mixed evenly to obtain an anti-caking and permeable pre-conditioning solution. The anti-caking and permeable pre-conditioning solution is evenly sprayed onto the pretreated silkworm excrement and mixed at 60°C for 10 minutes to ensure that the pre-conditioning solution evenly coats and wets the silkworm excrement particles, resulting in pre-conditioned silkworm excrement with a moisture content of approximately 40.7%.

[0066] Subsequently, a hydrothermal reaction medium was prepared, containing 0.12% citric acid and 0.25% potassium humate by mass, with the remainder being water. The pre-conditioned silkworm excrement and the hydrothermal reaction medium were added to a closed hydrothermal reactor at a mass ratio of 1:0.50, with a reactor loading coefficient of 60%. After the hydrothermal reactor was closed, the material temperature was raised to 160°C at a heating rate of approximately 5°C / min, the internal pressure of the reactor was controlled at a gauge pressure of 0.70 MPa, and subcritical hydrothermal treatment was carried out under low-speed stirring at 30 r / min for 30 min.

[0067] After processing, the material is cooled to a temperature suitable for solid-liquid separation, and then separated by spiral filter press to obtain a hydrothermal liquid phase and a permeable silkworm excrement solid phase with a water content of 56.0% and interconnected pores and liquid absorption capacity.

[0068] The organic nutrient mother liquor is prepared by mixing desalted plant-derived amino acid fermentation broth, humic acid broth, and seaweed extract in a mass ratio of 6:3:1. Before use, it is filtered through an 80-mesh sieve and homogenized to achieve the following results: pH 6.4, solid content 8.2%, total nitrogen content 1.45%, humic acid and fulvic acid combined content 1.8%, electrical conductivity 8.6 mS / cm, and viscosity 68 mPa·s at 25℃.

[0069] The permeable silkworm excrement solid phase and organic nutrient mother liquor were mixed at a mass ratio of 1:0.70 and subjected to vacuum-positive pressure pulse impregnation at 65°C: the internal pressure of the impregnation equipment was reduced to the gauge pressure of -0.055MPa and maintained for 6 minutes to allow air and some water vapor in the pores of the permeable silkworm excrement solid phase to be discharged; the internal pressure of the equipment was increased to the gauge pressure of 0.20MPa and maintained for 6 minutes to allow the organic nutrient mother liquor to enter the interior of the silkworm excrement particles under pressure; the vacuum and positive pressure impregnation process was repeated 3 times to obtain nutrient-loaded material with no obvious free liquid on the surface.

[0070] The obtained nutrient-loaded material was placed in a wet heat setting device and wet heat set at 125℃ and 0.35MPa gauge pressure for 20 minutes. After wet heat setting, the material was flash dehydrated using residual heat and then dried at 70℃ until the moisture content of the material was 18.4%. The dried material was then granulated by disc granulation and sieving to obtain granular silkworm excrement-based organic fertilizer with a particle size of 2.0mm to 5.0mm.

[0071] Example 2:

[0072] The difference from Example 1 is that: after the industrialized silkworm excrement is cleaned, broken up and screened, silkworm excrement with a particle size of 0.5mm to 2.5mm is taken and its moisture content is adjusted to 30.0% to obtain pretreated silkworm excrement.

[0073] Based on the dry weight of pretreated silkworm excrement, the amount of citric acid added to the anti-caking and permeability-enhancing preconditioning solution was 0.25%, potassium humate added was 0.25%, calcium lignosulfonate added was 0.06%, and the remainder was water; the pH of the anti-caking and permeability-enhancing preconditioning solution was 6.3, and the amount used was 12.0% of the dry weight of the pretreated silkworm excrement; the anti-caking and permeability-enhancing preconditioning solution was sprayed into the pretreated silkworm excrement and mixed at 48℃ for 6 min to obtain preconditioned silkworm excrement with a moisture content of approximately 35.1%.

[0074] The hydrothermal reaction medium contained 0.04% citric acid and 0.06% potassium humate, with the remainder being water. The mass ratio of pre-conditioned silkworm excrement to the hydrothermal reaction medium was 1:0.30. The subcritical hydrothermal treatment temperature was 140℃, the internal pressure of the reactor was 0.60 MPa (gauge pressure), and the treatment time was 22 min. The water content of the permeable silkworm excrement solid phase obtained after solid-liquid separation was 50.0%.

[0075] The organic nutrient mother liquor was prepared by mixing desalinated plant-derived amino acid fermentation broth and humic acid solution at a mass ratio of 7:3. Its pH was 5.8, solid content was 4.0%, total nitrogen content was 0.50%, and the combined content of humic acid and fulvic acid was 0.50%. The mass ratio of permeable silkworm excrement solid phase to organic nutrient mother liquor was 1:0.35, and the impregnation temperature was 55℃. The vacuum was drawn to a gauge pressure of -0.045MPa and held for 4 minutes, then the pressure was increased to a gauge pressure of 0.08MPa and held for 4 minutes. The vacuum-positive pressure pulse process was performed once.

[0076] The wet heat setting temperature was 108℃, the pressure was gauge pressure 0.18MPa, and the processing time was 12min. After wet heat setting, the product was dried at 60℃ until the moisture content was 20.0%. Granular silkworm excrement-based organic fertilizer with a particle size of 2.0mm to 4.0mm was obtained by disc granulation and sieving.

[0077] The remaining raw materials, operating steps, and process conditions are the same as in Example 1.

[0078] Example 3:

[0079] After impurities are removed, broken up, and sieved, silkworm excrement with a particle size of 2.0 mm to 6.0 mm is collected from industrially raised silkworms. Its moisture content is then adjusted to 42.0% to obtain pretreated silkworm excrement.

[0080] Based on the dry weight of pretreated silkworm excrement, the amount of malic acid added to the anti-caking and permeability-enhancing preconditioning solution was 1.50%, potassium humate was 1.20%, magnesium lignosulfonate was 0.50%, and the remainder was water; the pH of the anti-caking and permeability-enhancing preconditioning solution was 4.8, and the amount used was 30.0% of the dry weight of the pretreated silkworm excrement. The anti-caking and permeability-enhancing preconditioning solution was sprayed into the pretreated silkworm excrement and mixed at 68℃ for 15 min to obtain preconditioned silkworm excrement with a moisture content of approximately 49.0%.

[0081] The hydrothermal reaction medium contained 0.30% malic acid and 0.50% potassium humate, with the remainder being water. The mass ratio of pre-conditioned silkworm excrement to the hydrothermal reaction medium was 1:0.80. The subcritical hydrothermal treatment temperature was 168℃, the internal pressure of the reactor was 1.00 MPa (gauge pressure), and the treatment time was 35 min. The water content of the permeable silkworm excrement solid phase obtained after solid-liquid separation was 62.0%.

[0082] The organic nutrient mother liquor was prepared by mixing plant-derived amino acid fermentation broth, humic acid solution, and seaweed extract in a mass ratio of 5:4:1. Its pH was 7.2, solid content was 14.0%, total nitrogen content was 2.80%, and the combined content of humic acid and fulvic acid was 4.50%. The mass ratio of permeable silkworm excrement solid phase to organic nutrient mother liquor was 1:1.05, and the impregnation temperature was 60℃. The vacuum was drawn to a gauge pressure of -0.070MPa and held for 9 minutes, then the pressure was increased to a gauge pressure of 0.35MPa and held for 9 minutes. The vacuum-positive pressure pulse process was repeated 4 times.

[0083] The wet heat setting temperature is 142℃, the pressure is gauge pressure 0.55MPa, and the processing time is 32min. After wet heat setting, the product is dried at 82℃ until the moisture content is 14.0%. Granular silkworm excrement-based organic fertilizer with a particle size of 2.0mm to 5.0mm is obtained by drum granulation and sieving.

[0084] The remaining raw materials, operating steps, and process conditions are the same as in Example 1.

[0085] Example 4:

[0086] After impurities are removed, broken up, and sieved, silkworm excrement with a particle size of 0.8 mm to 5.0 mm is collected and its moisture content is adjusted to 36.0% to obtain pretreated silkworm excrement.

[0087] Based on the dry weight of pretreated silkworm excrement, the organic acid used in the anti-caking and permeability-enhancing preconditioning solution was lactic acid, with an addition amount of 0.75%; the humic component was potassium humate, with an addition amount of 0.55%; the non-sodium wetting and dispersing agent was potassium polyglutamate, with an addition amount of 0.12%, and the remainder was water. The pH of the anti-caking and permeability-enhancing preconditioning solution was 5.7, and the dosage was 22.0% of the dry weight of the pretreated silkworm excrement. The anti-caking and permeability-enhancing preconditioning solution was sprayed into the pretreated silkworm excrement and mixed at 58°C for 12 minutes to obtain preconditioned silkworm excrement with a moisture content of approximately 43.1%.

[0088] The hydrothermal reaction medium contained 0.10% lactic acid and 0.20% potassium humate, with the remainder being water. The mass ratio of pre-conditioned silkworm excrement to the hydrothermal reaction medium was 1:0.55. The subcritical hydrothermal treatment temperature was 155℃, the internal pressure of the reactor was 0.70 MPa (gauge pressure), the treatment time was 30 min, and the water content of the permeable silkworm excrement solid phase obtained after solid-liquid separation was 55.0%.

[0089] The organic nutrient mother liquor was prepared by mixing humic acid solution, desalinated plant-derived amino acid fermentation broth, and seaweed extract in a mass ratio of 5:4:1. Its pH was 6.8, solids content was 7.4%, total nitrogen content was 1.22%, the combined content of humic acid and fulvic acid was 2.30%, electrical conductivity was 8.0 mS / cm, and viscosity at 25℃ was 72 mPa·s. The mass ratio of permeable silkworm excrement solid phase to organic nutrient mother liquor was 1:0.65, and the impregnation temperature was 65℃. The vacuum was applied to a gauge pressure of -0.050 MPa and held for 6 minutes, then pressurized to a gauge pressure of 0.20 MPa and held for 6 minutes. This vacuum-positive pressure pulse process was repeated three times.

[0090] After vacuum-positive pressure pulse impregnation, 6.0% of mineral and adsorbent fertilizer-preserving conditioning components were added based on the dry weight of the nutrient-loaded material, including 4.0% calcium magnesium silicate and 2.0% dolomite powder. The calcium magnesium silicate and dolomite powder were pre-mixed evenly and then added to the nutrient-loaded material in batches and mixed for 15 minutes.

[0091] The wet heat setting temperature was 122℃, the pressure was 0.30MPa (gauge pressure), and the processing time was 22min. After wet heat setting, the product was dried at 68℃ until the moisture content was 17.5%. Granular silkworm excrement-based organic fertilizer with a particle size of 2.0mm to 5.0mm was obtained by extrusion granulation and sieving.

[0092] The remaining operating steps and process conditions are the same as in Example 1.

[0093] Example 5:

[0094] The difference from Example 1 is that after the vacuum-positive pressure pulse impregnation is completed, 6.0% of the total amount of adsorption and fertilizer retention conditioning component is added based on the dry weight of the nutrient load material. The adsorption and fertilizer retention conditioning component is composed of zeolite powder and bentonite in a mass ratio of 3:1. The zeolite powder and bentonite are pre-mixed evenly and then added to the nutrient load material in batches. The mixture is continuously mixed for 20 minutes to ensure that the adsorption and fertilizer retention conditioning component is evenly distributed on the surface of the material and between the particles.

[0095] The wet heat setting temperature is 130℃, the pressure is gauge pressure 0.40MPa, and the processing time is 25min. After wet heat setting, the product is dried at 72℃ until the moisture content is 16.5%. Then, it is shaped by extrusion granulation and screened to obtain columnar silkworm excrement-based organic fertilizer with a particle size of 2.0mm to 5.0mm.

[0096] The remaining raw materials, operating steps, and process conditions are the same as in Example 1.

[0097] Comparative Example 1:

[0098] The difference from Example 1 is that the anti-crusting and permeability pretreatment in step S2 is not performed. Instead, the pretreated silkworm excrement, after impurity removal, breaking, sieving, and moisture content adjustment, is directly added to the hydrothermal reaction medium described in Example 1 at a mass ratio of 1:0.50 into a closed hydrothermal reactor. Subcritical hydrothermal treatment is carried out at 160°C and a gauge pressure of 0.70 MPa for 30 minutes.

[0099] The solid-liquid separation, vacuum-positive pressure pulse impregnation, wet heat setting, drying and granulation steps are the same as in Example 1.

[0100] Comparative Example 2:

[0101] The difference from Example 1 is that calcium lignosulfonate is not added to the anti-crust permeability preconditioning solution in step S2, but is made up with an equal mass of water. That is, the anti-crust permeability preconditioning solution contains only citric acid, potassium humate and water.

[0102] Based on the dry weight of pretreated silkworm excrement, the amount of citric acid added remained at 0.80%, and the amount of potassium humate added remained at 0.60%; the pH, dosage, mixing temperature, and mixing time of the anti-crusting and permeability preconditioning solution were the same as in Example 1.

[0103] The remaining raw materials, operating steps, and process conditions are the same as in Example 1.

[0104] Comparative Example 3:

[0105] The difference from Example 1 is that: in step S2, citric acid is not added to the anti-crusting and permeability preconditioning solution, and the solution is made up with an equal mass of water; in step S3, citric acid is also not added to the hydrothermal reaction medium, and the solution is made up with an equal mass of water.

[0106] The remaining operating steps and process conditions are the same as in Example 1.

[0107] Comparative Example 4:

[0108] The difference from Example 1 is that potassium humate is not added to the anti-crusting and permeability preconditioning solution in step S2, and is instead made up with an equal mass of water; potassium humate is also not added to the hydrothermal reaction medium in step S3, and is instead made up with an equal mass of water. All other steps are the same as in Example 1.

[0109] Comparative Example 5:

[0110] The difference from Example 1 is that step S4 does not use vacuum-positive pressure pulse immersion, but uses atmospheric pressure immersion.

[0111] The permeable silkworm excrement solid phase was mixed with the organic nutrient mother liquor of Example 1 at a mass ratio of 1:0.70 and soaked at 65°C and normal pressure for 36 minutes. During the soaking process, the mixture was stirred at a low speed of 30 r / min to ensure that the organic nutrient mother liquor and the permeable silkworm excrement solid phase were in full contact. The remaining steps were the same as in Example 1.

[0112] Comparative Example 6:

[0113] The difference from Example 1 is that step S5 does not involve wet heat setting. After vacuum-positive pressure pulse impregnation in step S4, the resulting nutrient-loaded material is directly dried at 70°C until the material moisture content is 18.4%.

[0114] The dried material is directly subjected to disc granulation and screening to obtain granular silkworm excrement-based organic fertilizer with a particle size of 2.0mm to 5.0mm.

[0115] The remaining raw materials, operating steps, and process conditions are the same as in Example 1.

[0116] Comparative Example 7:

[0117] The difference from Example 1 is that: the conventional hydrothermal treatment and surface spraying of nutrient solution are used, but the anti-crusting and permeability pretreatment in step S2 is not performed, the vacuum-positive pressure pulse impregnation in step S4 is not used, and the wet heat setting in step S5 is not performed; the pretreated silkworm excrement after impurity removal, breaking, sieving and moisture content adjustment is directly added to the hydrothermal reaction medium described in Example 1 at a mass ratio of 1:0.50 into a closed hydrothermal reactor, and hydrothermal treatment is carried out at 160°C and a gauge pressure of 0.70 MPa for 30 minutes.

[0118] After hydrothermal treatment, solid-liquid separation was performed. The obtained silkworm excrement solid phase was mixed with the organic nutrient mother liquor from Example 1 at a mass ratio of 1:0.70. The organic nutrient mother liquor was sprayed evenly onto the surface of the silkworm excrement solid phase by spraying and mixed for 10 minutes under normal pressure. After mixing, without vacuum-positive pressure pulse impregnation and wet heat setting, the material was directly dried at 70°C until the moisture content was 18.4%. Subsequently, disc granulation and sieving were performed to obtain granular silkworm excrement-based organic fertilizer with a particle size of 2.0 mm to 5.0 mm.

[0119] The remaining raw materials and corresponding operating conditions are the same as in Example 1.

[0120] Each example and comparative example was prepared in three independent batches, and samples were taken from each batch for testing. For the surface dense layer coverage and internal dye penetration, 30 intact particles were randomly selected from each batch; for the internal nitrogen loading ratio, at least 50 intact particles were selected from each batch; for other quantitative indicators, at least two parallel samples were set for each batch. Quantitative test results are expressed as the average of the results from the three independent batches, rounded to one decimal place. Except for pH, fecal coliform count, and carbonization status, all other mass fractions and residues are calculated on a dry basis. The original MPN / g results for the fecal coliform count of the three independent batches are listed separately, without calculating the arithmetic mean.

[0121] Test method:

[0122] Surface dense layer coverage: Take the silkworm excrement solid phase after subcritical hydrothermal treatment and solid-liquid separation, and dry it at 60℃ to a moisture content of 18% to 22%. Randomly select 30 intact particles with a particle size of 1.0 mm to 4.0 mm from each batch, embed them in resin, and cut them along the center of the particle. The thickness of the slices is controlled to be 1.0 mm to 1.5 mm.

[0123] Particle cross-sectional images were acquired under fixed light source, fixed magnification, and fixed shooting parameters. Image analysis software was used to identify the continuous dense layer on the outer edge of the particles, and the ratio of the particle's outer perimeter length covered by the continuous dense layer to the total particle perimeter was calculated. The surface dense layer coverage rate was calculated using the following formula: Surface dense layer coverage rate = Continuous dense layer coverage length ÷ Total particle perimeter length × 100%; the lower the index, the lower the degree of continuous crusting and sealing on the particle surface.

[0124] Subcritical hydrothermal process screening test: Subcritical hydrothermal treatment was conducted on the same batch of industrially raised silkworm excrement at different temperatures, pressures, and treatment times; including: 142℃~145℃, pressure 0.6MPa, treatment time 30min; 160℃~165℃, pressure 1.5MPa, treatment time 30min; 162℃~166℃, pressure 1.55MPa, treatment time 70min; 180℃~185℃, pressure 2.5MPa, treatment time 30min. min; the treated sample was dried to constant weight at 60℃, pulverized and passed through a 0.5mm sieve, 5.000g of dry sample was weighed, 50.0mL of deionized water was added, and the sample was shaken at 25℃ and 180r / min for 60min. It was then centrifuged at 8000×g for 10min, and the supernatant was filtered through a 0.45μm filter membrane. 20.0mL of filtrate was taken and dried to constant weight at 105℃, and the mass of the residue was recorded. Subsequently, the sample was ignited at 550℃ to constant weight, and the ash mass was recorded.

[0125] The mass fraction of water-soluble organic matter is calculated using the following formula: Wherein, Ws is the mass fraction of water-soluble organic matter, in %; m1 is the mass of residue after drying the filtrate at 105℃, in g; m2 is the mass of ash after ignition of the residue at 550℃, in g; V is the total volume of the extract, in mL; V1 is the volume of filtrate taken during the determination, in mL; and m is the dry weight of the test sample, in g.

[0126] Meanwhile, the appearance of the processed material was observed and recorded under uniform lighting conditions, and the carbonization was divided into the following three levels: no obvious carbonization, local color deepening, and obvious carbonization.

[0127] Internal dye penetration rate: Take the silkworm excrement solid phase obtained after solid-liquid separation in step S3, dry it at 60℃ to a moisture content of 20%±2%, and seal it for equilibration for 24h; weigh 20.00g of sample for each batch, add 200mL of 0.10% Brilliant Blue FCF aqueous solution, and let it stand and soak for 10min at 25℃ and normal pressure.

[0128] After soaking, the sample was placed on a sieve to drain for 2 minutes, and then centrifuged at 300×g for 2 minutes to remove the free dye attached to the particle surface. 30 intact particles with a particle size of 1.0 to 4.0 mm were randomly selected from each batch and cut along the geometric center of the particle.

[0129] Images of particle cross sections were acquired under fixed light source, fixed shooting distance, and 20x magnification. ImageJ image analysis software or software with similar functions were used to identify the blue dyeing area inside the particle cross section. The image recognition threshold was determined based on the blank silkworm excrement cross section that was not soaked in dye solution and remained consistent throughout the image analysis of each embodiment and comparative example. The internal dye penetration rate was calculated as follows: Internal dye penetration rate = dyed area inside the particle cross section ÷ total area of ​​the particle cross section × 100%.

[0130] Residual levels of target antibiotics inside the particles: Oxytetracycline, tetracycline, sulfadiazine, sulfamethoxazole, erythromycin, and tylosin were selected as target antibiotics. The residual levels of target antibiotics inside the particles of untreated industrially raised silkworm excrement and silkworm excrement treated in step S3 were tested. The material of about 0.3 mm thickness on the outer surface of the particles was removed by mechanical cutting or fine grinding. The internal part of the particles was collected, and the obtained internal sample was freeze-dried or vacuum-dried at a temperature not exceeding 50°C. The sample was then pulverized and mixed evenly.

[0131] Weigh 2.00 g of sample and add 10.0 mL of an extraction solution composed of acetonitrile, water, and formic acid in a volume ratio of 80:19:1. Vortex mix for 1 min, sonicate for 30 min, and then centrifuge at 10000×g for 10 min. Collect the supernatant, purify it using a solid-phase extraction column, concentrate it under nitrogen blowing, and make up to a fixed volume. Filter it through a 0.22 μm filter membrane and analyze it using liquid chromatography-tandem mass spectrometry.

[0132] The liquid chromatography-tandem mass spectrometry (LC-MS / MS) test conditions are as follows: the chromatographic column is a C18 column with a size of 2.1 mm × 100 mm and a packing particle size of no more than 3 μm; mobile phase A is an aqueous solution containing 0.1% formic acid, and mobile phase B is acetonitrile; the flow rate is 0.30 mL / min; and detection is performed using an electrospray ionization source and multiple reaction monitoring (MRM) mode.

[0133] For each target antibiotic, a calibration curve was established using no fewer than five concentration points, with a correlation coefficient of no less than 0.995. The spiked recovery rate was controlled at 70%–120%. The relative standard deviation of parallel sample determinations was no more than 20%. The total residual amount of the target antibiotic inside the particle was the sum of the contents of each quantitatively detected target antibiotic, expressed in μg / kg, with one decimal place. A target antibiotic was recorded as "<LOQ" when its concentration was below the limit of quantitation; and as "not detected" when its concentration was below the limit of detection.

[0134] Fecal coliform count: The final fertilizer products prepared in each example and comparative example were tested on the first day after the product preparation was completed. Fecal coliform count was determined according to GB / T19524.1—2004 "Determination of Fecal Coliform in Fertilizers". A representative 10.0g sample of the finished product was weighed, added to 90mL of sterile diluent, shaken thoroughly and homogenized to obtain an initial sample suspension. The sample suspension was then serially diluted tenfold and tested using the multi-tube fermentation maximum probability method.

[0135] Three independent batches were tested for each example or comparative example. The test results were reported according to the maximum probable number lookup table specified in the standard, in MPN / g, without artificially increasing the number of decimal places.

[0136] Internal nitrogen loading ratio: Take the permeable silkworm excrement solid phase before impregnation in step S4 and the nutrient-loaded material after impregnation, respectively, and dry them to constant weight by freeze drying or vacuum drying at no higher than 60℃; randomly select no less than 50 whole particles from each batch, remove the surface layer of about 0.3 mm thick from the outer surface of the particles by mechanical grinding or cutting, collect the samples of the internal part of the particles and the whole particles, and determine the dry basis weight of the corresponding samples; the total nitrogen content of the internal part of the particles and the whole particles samples is determined according to NY / T2542—2014 "Determination of Total Nitrogen Content in Fertilizers".

[0137] Basic physicochemical indicators of the finished product: The final fertilizer products obtained from each example and comparative example were pulverized and mixed evenly after reduction, and used for testing of organic matter, total nitrogen, total phosphorus, and total potassium content. The organic matter content was determined according to the method specified in NY / T 525—2021; the total nitrogen content was determined according to NY / T 2542—2014; the total phosphorus content was determined according to NY / T 2541—2014 and calculated as P2O5; and the total potassium content was determined according to NY / T 2540—2014 and calculated as K2O.

[0138] Finished product pH: Weigh 10.00g of the final fertilizer sample after thorough mixing, add 100.0mL of deionized water, shake at 25℃ and 180r / min for 30min, let stand for 30min, and then measure the pH of the supernatant using a pH meter calibrated with a standard buffer solution; the mass-volume ratio of sample to water is 1g:10mL, and each batch is measured twice in parallel, with the results retained to one decimal place.

[0139] Total nitrogen leaching rate over 24 hours: Weigh 10.00 g of the final fertilizer sample (dry basis) into a stoppered container, add 200.0 mL of deionized water, and extract by shaking at 25 °C and 150 r / min for 24 hours. After extraction, centrifuge at 8000 × g for 10 min, collect the supernatant and filter it through a 0.45 μm filter membrane. The total nitrogen concentration in the extract was determined according to HJ636—2012 "Determination of Total Nitrogen in Water by Alkaline Potassium Persulfate Digestion Ultraviolet Spectrophotometry". The total nitrogen mass fraction of the pre-extracted sample was determined according to NY / T2542—2014.

[0140] After extraction, the total nitrogen concentration in the extract was measured, and a deionized water blank was set up. The 24-hour total nitrogen leaching rate was calculated using the following formula: 24-hour total nitrogen leaching rate = (24-hour total nitrogen mass in the extract ÷ total nitrogen mass in the pre-extraction fertilizer sample) × 100%. The total nitrogen mass in the extract was calculated based on the total nitrogen concentration after deducting the blank and the actual volume of the extract; the total nitrogen mass in the pre-extraction sample was calculated based on the dry basis mass of the sample and the total nitrogen mass fraction.

[0141] Test results:

[0142] Table 1 - Predicted results of solid phase structure, dissolution, and harmlessness after subcritical hydrothermal treatment.

[0143] sample Surface dense layer coverage (%) Water-soluble organic matter (%) Carbonization Internal dye penetration rate (%) Total residual amount of the target antibiotic inside the particle (μg / kg) Example 1 13.8 35.8 No obvious carbonization 72.4 Not detected Example 2 24.6 23.8 No obvious carbonization 55.8 <LOQ Example 3 9.2 39.1 The color was noticeably darker in some areas. 84.6 Not detected Example 4 14.5 33.6 No obvious carbonization 73.5 Not detected Example 5 13.6 35.7 No obvious carbonization 72.1 Not detected Comparative Example 1 47.8 28.4 The color was noticeably darker in some areas. 31.7 18.6 Comparative Example 2 28.9 31.2 No obvious carbonization 59.4 7.4 Comparative Example 3 38.6 27.6 The color was noticeably darker in some areas. 43.8 12.8 Comparative Example 4 34.2 29.3 The color was noticeably darker in some areas. 48.9 10.1 Comparative Example 5 13.9 35.8 No obvious carbonization 72.2 Not detected Comparative Example 6 13.7 35.8 No obvious carbonization 72.3 Not detected Comparative Example 7 48.5 28.3 The color was noticeably darker in some areas. 30.8 22.3

[0144] Table 2 - Predicted results of nutrient content, load retention, and hygiene safety of the final silkworm excrement-based organic fertilizer

[0145] sample Organic matter (%) Total nitrogen (%) <![CDATA[Total phosphorus P₂O₅ (%)]]> <![CDATA[Total potassium K2O (%)]]> Nitrogen + Phosphorus + Potassium (%) pH (1:10) Fecal coliform count (3 batches, MPN / g) Internal nitrogen loading percentage (%) Total nitrogen leaching rate in 24 hours (%) Example 1 72.8 4.9 1.5 3.7 10.1 6.4 <3、<3、<3 73.6 10.8 Example 2 71.4 4.5 1.4 3.4 9.3 6.1 <3、3、<3 54.8 15.6 Example 3 74.2 5.6 1.6 4.0 11.2 6.5 <3、<3、<3 82.1 12.7 Example 4 68.9 4.7 1.5 3.6 9.8 6.9 <3、<3、<3 75.4 8.9 Example 5 68.5 4.6 1.5 3.6 9.7 6.6 <3、<3、<3 73.2 6.4 Comparative Example 1 71.6 4.7 1.5 3.6 9.8 6.3 <3、<3、<3 48.9 18.7 Comparative Example 2 72.0 4.8 1.5 3.7 10.0 6.4 <3、<3、<3 61.7 15.2 Comparative Example 3 71.2 4.6 1.5 3.5 9.6 7.0 <3、<3、<3 57.3 16.9 Comparative Example 4 71.5 4.7 1.5 3.2 9.4 6.1 <3、<3、<3 59.4 16.1 Comparative Example 5 72.7 4.9 1.5 3.7 10.1 6.4 <3、<3、<3 36.8 22.8 Comparative Example 6 72.9 5.1 1.5 3.7 10.3 6.4 3、9、3 73.1 31.6 Comparative Example 7 71.4 5.0 1.5 3.6 10.1 6.3 43、93、43 21.4 38.7

[0146] As shown in Table 1, the surface dense layer coverage of the silkworm excrement solid phase obtained in Examples 1 to 5 ranged from 9.2% to 24.6%, the internal dye penetration rate ranged from 55.8% to 84.6%, and the mass fraction of water-soluble organic matter ranged from 23.8% to 39.1%. The surface dense layer coverage of Examples 1, 4, and 5 was 13.8%, 14.5%, and 13.6%, respectively, and the internal dye penetration rates were 72.4%, 73.5%, and 72.1%, respectively. No obvious carbonization was observed in the treated materials. The surface dense layer coverage of Example 2 was 24.6%, the internal dye penetration rate was 55.8%, and the mass fraction of water-soluble organic matter was 23.8%. The permeability indicators were lower than those of other examples, but an internal dye penetration area could still be formed. The surface dense layer coverage of Example 3 was the lowest at 9.2%, while the internal dye penetration rate and the mass fraction of water-soluble organic matter were the highest at 84.6% and 39.1%, respectively. At the same time, there was a significant local color deepening.

[0147] The results of the detection of total residual target antibiotics inside the particles showed that no antibiotics were detected in Examples 1, 3, 4 and 5, and the amount in Example 2 was below the limit of quantification. This indicates that under the conditions of anti-crusting and permeability preconditioning and subcritical hydrothermal treatment specified in each example, the continuous dense layer on the surface of the silkworm excrement particles was suppressed, the degree of liquid phase permeation inside the particles was increased, and the residual amount of target antibiotics inside the particles was maintained at a low level.

[0148] Comparative Example 1, without the anti-crusting and permeability pretreatment in step S2, had a surface dense layer coverage of 47.8%, which was 34.0 percentage points higher than Example 1; the internal dye penetration rate was 31.7%, which was 40.7 percentage points lower than Example 1; the total residual amount of the target antibiotic inside the particles was 18.6 μg / kg, and there was a significant local darkening of color. Comparative Example 7, without anti-crusting and permeability pretreatment, vacuum-positive pressure pulse impregnation, and wet heat setting, had a surface dense layer coverage of 48.5%, an internal dye penetration rate reduced to 30.8%, and a total residual amount of the target antibiotic inside the particles of 22.3 μg / kg. This indicates that silkworm excrement without anti-crusting and permeability pretreatment is prone to forming a continuous dense layer during hydrothermal treatment, and the degree to which the hydrothermal reaction medium penetrates into the particles is reduced.

[0149] Comparative Example 2, without the addition of calcium lignosulfonate to the anti-crust permeability preconditioning solution, had a surface dense layer coverage of 28.9%, an internal dye penetration rate of 59.4%, and a total residual amount of the target antibiotic inside the granules of 7.4 μg / kg. Comparative Example 3, without the addition of citric acid to either the anti-crust permeability preconditioning solution or the hydrothermal reaction medium, had a surface dense layer coverage of 38.6%, an internal dye penetration rate of 43.8%, and a total residual amount of the target antibiotic inside the granules of 12.8 μg / kg. Comparative Example 4, without the addition of potassium humate to either the anti-crust permeability preconditioning solution or the hydrothermal reaction medium, had a surface dense layer coverage of 34.2%, an internal dye penetration rate of 48.9%, and a total residual amount of the target antibiotic inside the granules of 10.1 μg / kg. The results of Comparative Examples 2 to 4 were all lower than those of Example 1, indicating that organic acids, potassium humate or potassium fulvate and non-sodium wetting and dispersing agents play different roles, and the absence of any component will reduce the internal mass transfer effect of subsequent subcritical hydrothermal treatment.

[0150] The organic acids in the anti-caking and permeability-enhancing pre-conditioning solution maintain a weakly acidic to near-neutral environment on the surface of the silkworm excrement particles and soften the surface organic cement structure, reducing the rapid browning and adhesion of proteins, sugars, and fiber components during the heating stage. Potassium humate or potassium fulvate disperses small-molecule organic matter and colloidal substances generated during hydrothermal treatment, reducing the degree of re-aggregation of colloidal substances on the particle surface and in the internal pores. Non-sodium wetting and dispersing agents improve the spreading of the anti-caking and permeability-enhancing pre-conditioning solution on the particle surface, allowing the liquid phase to enter the shallow pores of the particles.

[0151] Example 2, using lower effective component addition, hydrothermal reaction medium dosage, subcritical hydrothermal treatment temperature, and treatment time, showed a relatively high surface dense layer coverage, but relatively low internal dye penetration and water-soluble organic matter mass fraction, indicating that the openness of the internal pores of the particles was limited under lower treatment intensity. Example 3, by increasing the effective component addition, hydrothermal reaction medium dosage, treatment temperature, and treatment time, further reduced the surface dense layer coverage and further increased the internal dye penetration and water-soluble organic matter mass fraction, but the material showed a significant local color deepening, indicating that further increasing the treatment intensity may increase local browning and the tendency for overtreatment.

[0152] As shown in Table 2, the organic matter content of the silkworm excrement-based organic fertilizers obtained in Examples 1 to 5 ranges from 68.5% to 74.2%, the total nitrogen content ranges from 4.5% to 5.6%, the total phosphorus content ranges from 1.4% to 1.6%, the total potassium content ranges from 3.4% to 4.0%, the total nitrogen, phosphorus, and potassium content ranges from 9.3% to 11.2%, and the pH ranges from 6.1 to 6.9.

[0153] Example 1 had an internal nitrogen loading ratio of 73.6% and a total nitrogen leaching rate of 10.8% over 24 hours. Example 2 had an internal nitrogen loading ratio of 54.8% and a total nitrogen leaching rate of 15.6% over 24 hours, corresponding to its high surface dense layer coverage and low internal dye penetration. Example 3 had the highest internal nitrogen loading ratio at 82.1%, indicating that higher particle internal permeability and stronger vacuum-positive pressure pulse impregnation conditions could improve the degree to which the organic nutrient mother liquor penetrated into deep pores. Example 4 had an internal nitrogen loading ratio of 75.4% and a total nitrogen leaching rate of 8.9% over 24 hours. Example 5 had an internal nitrogen loading ratio of 73.2%, close to that of Example 1, but its total nitrogen leaching rate was reduced to 6.4% over 24 hours, the lowest among all samples.

[0154] Comparative Examples 1 to 4 all employed vacuum-positive pressure pulse impregnation, but the internal nitrogen loading ratio was only 48.9% to 61.7%, lower than that of Example 1. The reason for this is the lack of corresponding technical features in step S2 or step S3, which increased the surface dense layer coverage of the obtained silkworm excrement solid phase and decreased the internal dye penetration rate. The anti-crusting permeability preconditioning and subcritical hydrothermal treatment form a permeable silkworm excrement solid phase with interconnected pores and liquid absorption capacity, which is the structural basis for subsequent organic nutrient mother liquor infiltration loading.

[0155] Comparative Example 5 used atmospheric pressure immersion instead of vacuum-positive pressure pulse impregnation. Its surface dense layer coverage and internal dye penetration were basically the same as in Example 1, but the internal nitrogen loading ratio decreased from 73.6% to 36.8%, and the total nitrogen leaching rate after 24 hours increased from 10.8% to 22.8%. During atmospheric pressure immersion, residual air inside the permeable silkworm excrement solid phase was not fully expelled, and the organic nutrient mother liquor remained mostly on the outer surface of the particles and in shallow pores. Vacuum-positive pressure pulse impregnation expelled air and some water vapor from the pores through the vacuum stage, and then pushed the organic nutrient mother liquor into deeper pores through the positive pressure stage. Multiple pulses improved the depth and uniformity of nutrient loading and reduced the problem of nutrient components mainly remaining on the particle surface.

[0156] Comparative Example 6, without hydrothermal setting, had an internal nitrogen loading of 73.1%, similar to Example 1, but its total nitrogen leaching rate increased to 31.6% over 24 hours. This indicates that vacuum-positive pressure pulse impregnation determines the extent to which the organic nutrient mother liquor penetrates the particles, while hydrothermal setting determines whether the nutrient components that have penetrated the particles can be stably maintained. Hydrothermal setting causes humic acid, fulvic acid, amino acids, small molecule organic acids, ammonium nitrogen, and soluble potassium salts to adsorb, complex, hydrogen-bond, and partially condense with cellulose, hemicellulose, chitin hydrolysates, and mineral ash in the silkworm excrement particles. This transforms the nutrient components from a liquid-filled state to a state maintained by a porous network and organic colloids, thereby reducing short-term nutrient leaching under water immersion conditions.

[0157] In Example 4, after adding minerals and adsorbent fertilizer-retaining conditioning components, the total nitrogen leaching rate was reduced to 8.9% in 24 hours. In Example 5, after adding conditioning components composed of zeolite powder and bentonite, the internal nitrogen loading ratio was similar to that in Example 1, but the total nitrogen leaching rate was further reduced to 6.4% in 24 hours. This improved the adsorption and retention of nutrient components on the material surface and between particles, without changing the permeable structure formed in step S3, and without replacing the effect of vacuum-positive pressure pulse impregnation on the internal loading.

[0158] Comparative Example 7 adopted a conventional hydrothermal treatment, surface spraying of organic nutrient mother liquor, and direct drying route. Its total nitrogen, phosphorus, and potassium nutrient content was 10.1%, the same as in Example 1, but the internal nitrogen loading ratio was only 21.4%, and the total nitrogen leaching rate reached 38.7% in 24 hours. This indicates that the similar total nutrient content of the finished product does not mean that the nutrient loading state and retention capacity are similar. Without anti-crusting and permeability pre-conditioning, the internal channels of the particles are not sufficiently open; without vacuum-positive pressure pulse impregnation, the organic nutrient mother liquor mainly stays on the outer surface of the particles; without wet heat setting, the soluble nutrient components that enter the pores do not form a stable retention state.

[0159] Based on the results in Tables 1 and 2, the anti-crust permeability preconditioning reduces the coverage of the dense surface layer, subcritical hydrothermal treatment opens and connects the internal mass transfer channels of the particles, vacuum-positive pressure pulse impregnation increases the internal nitrogen loading ratio, wet heat setting reduces the total nitrogen leaching rate over 24 hours, and mineral and adsorbent fertilizer-retaining conditioning components further enhance nutrient retention capacity. The particle structure formed in the preceding steps directly affects the nutrient loading effect of the subsequent steps, and a continuous technical interaction relationship is formed between the steps, enabling industrialized silkworm excrement to reduce internal risk factors while achieving internal loading and stable maintenance of organic nutrient mother liquor.

[0160] Based on the preferred embodiments of the present invention described above, and through the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A method for preparing organic fertilizer from subcritical water used in industrialized silkworm excrement farming in a harmless and resource-efficient manner, characterized in that, include: S1: The silkworm excrement from industrialized breeding is subjected to impurity removal, breaking down, screening and moisture content adjustment to obtain pretreated silkworm excrement; S2: Pretreated silkworm excrement is mixed with an anti-crusting and permeability preconditioning solution containing organic acids, potassium humate or potassium fulvate, non-sodium wetting and dispersing agent and water to obtain preconditioned silkworm excrement; S3: Pre-conditioned silkworm excrement and a hydrothermal reaction medium containing organic acids and potassium humate or potassium fulvate are placed in a closed hydrothermal reactor. Subcritical hydrothermal treatment is carried out at 135℃~175℃, with a pressure of 0.60MPa~1.80MPa gauge pressure inside the reactor, and the hydrothermal reaction medium is kept in a continuous liquid phase at the corresponding treatment temperature. After solid-liquid separation, a permeable silkworm excrement solid phase is obtained. S4: Vacuum-positive pressure pulse impregnation of permeable silkworm excrement solid phase with organic nutrient mother liquor to obtain nutrient-loaded material; S5: The nutrient-loaded material is subjected to wet heat setting, drying and molding treatment to obtain silkworm excrement-based organic fertilizer.

2. The method for preparing organic fertilizer from subcritical water of industrialized silkworm excrement according to claim 1, characterized in that: In step S1, the pretreated silkworm excrement has a particle size of 0.5 mm to 6.0 mm and a moisture content of 25% to 45%.

3. The method for preparing organic fertilizer from subcritical water of industrialized silkworm excrement according to claim 1, characterized in that: In step S2, the organic acid is one or more of citric acid, malic acid, and lactic acid; the potassium humate or potassium fulvate is a water-soluble potassium source of humic acid or fulvate; and the non-sodium wetting and dispersing agent is one or more of calcium lignosulfonate, magnesium lignosulfonate, ammonium lignosulfonate, potassium polyglutamate, calcium polyglutamate, magnesium polyglutamate, and molasses fermentation broth concentrate.

4. The method for preparing organic fertilizer from subcritical water of industrialized silkworm excrement according to claim 1, characterized in that: In step S2, based on the dry weight of pretreated silkworm excrement, the amount of organic acid added is 0.2%–1.5%, the amount of potassium humate or potassium fulvate added is 0.2%–1.2%, and the amount of non-sodium wetting and dispersing agent added is 0.05%–0.5%; the pH of the anti-caking and permeability preconditioning solution is 4.8–6.5, and the amount used is 8%–35% of the dry weight of pretreated silkworm excrement, and the moisture content of the preconditioned silkworm excrement is 35%–55%.

5. The method for preparing organic fertilizer from subcritical water of industrialized silkworm excrement according to claim 1, characterized in that: In step S3, the hydrothermal reaction medium includes 0.03% to 0.30% organic acid and 0.05% to 0.50% potassium fulvate or potassium humate, with the remainder being water; the mass ratio of pre-conditioned silkworm excrement to the hydrothermal reaction medium is 1:(0.25 to 0.80).

6. The method for preparing organic fertilizer from subcritical water of industrialized silkworm excrement according to claim 1, characterized in that: In step S4, the organic nutrient mother liquor is prepared from one or more of the following: hydrothermal effluent from livestock and poultry manure, concentrated biogas slurry, amino acid fermentation broth, humic acid broth, and seaweed extract; the organic nutrient mother liquor has a pH of 5.5 to 7.5, a solid content of 3% to 15%, a total nitrogen content of 0.3% to 3.0%, and a humic acid or fulvic acid content of 0.2% to 5.0%.

7. The method for preparing organic fertilizer from subcritical water of industrialized silkworm excrement according to claim 1, characterized in that: In step S4, the mass ratio of the permeable silkworm excrement solid phase to the organic nutrient mother liquor is 1:(0.3~1.2), and the impregnation temperature is 50℃~85℃.

8. The method for preparing organic fertilizer from subcritical water of industrialized silkworm excrement according to claim 1, characterized in that: The vacuum-positive pressure pulse impregnation process in step S4 includes: evacuating to a gauge pressure of -0.08MPa to -0.04MPa and holding for 3 to 10 minutes; increasing the pressure to a gauge pressure of 0.05MPa to 0.40MPa and holding for 3 to 10 minutes; the evacuation and pressure increase process is repeated 1 to 4 times.

9. The method for preparing organic fertilizer from subcritical water of industrialized silkworm excrement according to claim 1, characterized in that: In step S5, the wet heat setting temperature is 105℃~145℃, the pressure is gauge pressure 0.15MPa~0.60MPa, and the processing time is 10min~35min; the drying temperature is 55℃~85℃, and the product moisture content is dried to 12%~25%. After drying, the material is subjected to disc granulation, extrusion granulation, drum granulation or screening to obtain granular or powdered silkworm excrement-based organic fertilizer.

10. The method for preparing organic fertilizer from subcritical water of industrialized silkworm excrement according to claim 1, characterized in that: After the vacuum-positive pressure pulse impregnation in step S4 and before the wet heat setting in step S5, minerals and adsorbent fertilizer-retaining conditioning components are added to the nutrient-loaded material. The minerals and adsorbent fertilizer-retaining conditioning components are one or more of calcium silicate, magnesium silicate, calcium magnesium silicate, dolomite powder, diatomaceous earth, sepiolite powder, zeolite powder, bentonite, and biochar powder. The amount added is 1.0% to 10.0% of the dry basis mass of the nutrient-loaded material.